Pengembangan E-Modul Berbasis Flip PDF Professional pada Materi Gaya dan Perubahan Energi Kelas IV SDN Sepatan 3 Kabupaten Tangerang - Fadilah, Ahmad Arif; Latifah, Nur; Safitri, Agustini (Program Studi PGMI Sekolah Tinggi Ilmu Tarbiyah Nahdlatul Ulama Al Hikmah Mojokerto, 2024)
Research with the development of a Professional Flip Pdf based E-Module on Force and Energi Changes for Class IV SDN Sepatan 3 Tangerang Regency in this learning aims to produce a product in the science subject. This development uses the ADDIE model procedure with 5 stages, namely: Analysis, Design, Development, Implementation, and Evaluation. This development also went through a validation stage with material experts, namely by getting a percentage result of 86% with the criteria